(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Labour is a very short period of life of a fetus but poses physiological stress to all the fetus. Fetal distress is a progressive condition that, if not corrected, can increase the chance of fetal death. So routine and continuous monitoring of fetal heart rate by doing Cardiotocography in labour in high risk pregnancies has become an established obstetric practice. The aim of the study is to evaluate the predictive value of the admission CTG in detecting fetal hypoxia at the time of admission during labour and to correlate its result with fetal outcome in high risk pregnancies. Materials and methods: This prospective observational study was held in ChattogramMaa O Shishu Hospital Medical College from March 2022 to August 2022. A total of 65 gravid women with high risk pregnancies of >37 weeks gestation with cephalic presentation in the first stage of labour were taken. Result was assessed in the form of APGAR SCORE at 5 min, NICU admission, perinatal mortality and mode of delivery. Statistical analysis was done by using SPSS 20. Chi square test was used and p< 0.05 is considered statistically significant. Results: A total of 65 high risk obstetric patients were recruited. The admission CTG were reactive in 45 patients (69.23%) and non-reactive in 20 patients (30.77%). APGAR SCORE <7 at 5 minutes was higher in nonreactive group (60%) as compared to reactive group (60% v/s 17.78%). Occurrence of fetal distress, NICU admission and perinatal mortality was also higher in nonreactive group to reactive group (NICU admission 35% v/s 6.67% and perinatal mortality 15% v/s 0%). Incidence of vaginal delivery vaginal delivery was more common when the test was reactive (64.44% v/s 10%). Sensitivity, specificity, positive predictive value and negative predictive value of Admission CTG for these high risk cases were 68%, 76%, 54% and 85% respectively. Conclusion: Admission CTG is a simple and easy test and an effective screening test to identify groups of women with greater risk of intrapartum fetal hypoxia and to predict fetal outcome and thus prevents unnecessary delay in intervention. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 91-95